THE ROLE AND IMPORTANCE OF ENGLISH LANGUAGE IN MEDICAL EDUCATION (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2026)
This article explores the role and importance of the English language in medical education. English has become a global language of science and medicine, providing access to the latest research, clinical guidelines, and international medical communication. The study analyzes how English language proficiency contributes to the development of medical students’ academic knowledge, clinical thinking, and professional communication skills. Particular attention is given to the integration of English into medical curricula and its impact on understanding medical terminology and scientific literature. The results indicate that English language competence significantly improves students’ ability to engage with global medical knowledge and enhances their overall educational performance.